Emerging roles of long noncoding and circular RNAs in pancreatic ductal adenocarcinoma - Sato, Hiromichi; Hara, Tomoaki; Tatekawa, Shotaro; Sasaki, Kazuki; Kobayashi, Shogo; Kitagawa, Toru; Doki, Yuichiro; Eguchi, Hidetoshi; Ogawa, Kazuhiko; Uchida, Shizuka; Ishii, Hideshi (Frontiers in Physiology, 2022)
An international project on the human genome revealed that various RNAs (e.g., messenger RNAs, microRNAs, and long noncoding RNAs [lncRNAs] and their subclass circular RNA [circRNA)) are involved in the pathogenesis of different human diseases, including cancer. Recent studies have highlighted the critical roles of lncRNAs and circRNA in pancreatic ductal adenocarcinoma (PDAC), especially in the epithelial–mesenchymal transition, a phenomenon regulating cancer metastasis. Growing research in this field has indicated that the tertiary structure of lncRNAs supposedly regulates biological function via RNA–RNA or RNA–protein associations, aiding early diagnosis and therapy selection for various diseases, including cancer. Here we describe the emerging roles of ncRNAs in PDAC and highlight how these ncRNAs can be used to detect and control this intractable cancer.